Francesco Soriano: Magnificat Primi Toni [odd verses] - Henriques, Luís (2022)
Edition of the "Magnificat Primi Toni", for four voices, by the Italian composer Francesco Soriano (c.1548-1621). This work sets the polyphony for the odd verses of the canticle. It was published in Soriano's collection "Passio D. N. Jesu Christi secundum quatuor evangelistas... Magnificat sexdecim...", printed in Rome by Luca Antonio Soldi in 1619.